Influence of Enclosure Size on Growth of Breast and Leg Muscle Fibers in Domestic Fowl - Alves, Michaela F.R.; Abe, Flavia R.; Boleli , Isabel C. (International Journal of Poultry Science, 2012)
This experiment evaluated the growth of breast and leg muscle fibers of domestic fowl raised in two enclosure sizes (SE: Small Enclosure, 1.125 m2/10 birds; LE: Large Enclosure, 5.25 m2/10 birds). In breast muscles, the number of fibers per area decreased over time and higher values were observed in broilers housed in SE compared to LE. The fiber size increased with age and was greater in LE than SE at 56 days of age, suggesting greater hypertrophic growth of fibers in breast muscle for broilers maintained in LE. In leg muscles, the muscle cross-sectional area was greater for broilers raised in LE than SE at 56 days of age and decreased from 42 to 56 days of age in broilers raised in SE, suggesting leg muscle atrophy in these birds. The Fast Glycolytic (FG), Fast Oxidative-Glycolytic (FOG) and Slow Oxidative (SO) fibers grew until 42 days of age in both enclosure sizes. The area of FOG fibers was greater in broilers raised in LE than those in SE at 28 and 56 days of age; in LE-raised broilers, the SO area was greater at 28, 42 and 56 days of age, suggesting that the muscles of broilers housed in LE are more oxidative. The BW gain was greater for broilers raised in LE than SE, whereas BW, feed intake and feed conversion were not influenced by enclosure size. Thus, the enclosure space affected hypertrophic growth and metabolic characteristics of breast and leg muscle fibers.